2008
DOI: 10.1152/ajplung.00439.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-mediated inflammatory and oxidative responses are strain-dependent in mice

Abstract: A variety of mouse models have been used to study the pathogenesis of pulmonary emphysema/chronic obstructive pulmonary disease. The effect of cigarette smoke (CS) is believed to be strain dependent, because certain mouse strains are more susceptible or resistant to development of emphysema. However, the molecular basis of susceptibility of mouse strains to effects of CS is not known. We investigated the effect of CS on lungs of most of the commonly used mouse strains to study the molecular mechanism of suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
167
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(189 citation statements)
references
References 53 publications
20
167
2
Order By: Relevance
“…In contrast, the number of macrophages was not altered after 3-d CS exposure, whereas subchronic and chronic CS exposure induced a significant increase in macrophages influx in BAL fluid of C57BL/6J mice. These discrepancies are likely caused by differences in CS doses, and pattern/composition of smoke delivered by different CS generating systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the number of macrophages was not altered after 3-d CS exposure, whereas subchronic and chronic CS exposure induced a significant increase in macrophages influx in BAL fluid of C57BL/6J mice. These discrepancies are likely caused by differences in CS doses, and pattern/composition of smoke delivered by different CS generating systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…All animal procedures described in this study were approved by the University Committee on Animal Research Committee of the University of Rochester. For studies involving 3-d CS exposure, research-grade cigarettes (3R4F; University of Kentucky, Lexington, KY) were used to generate smoke, and 8-wk-old male mice were exposed to mainstream CS using a BaumgartnerJaeger CSM2072i automatic CS generating machine (CH Technologies) as described previously (31). The smoke concentration was set at a value of approximately 300 mg TPM/m 3 (31,37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term COPD includes at least two main lung diseases: chronic bronchitis and emphysema, both accompanied by airways remodelling and abnormal inflammatory responses of the lungs. Increased numbers of neutrophils, macrophages and inflammatory mediators are observed in the sputum and bronchoalveolar lavage fluid of COPD patients as well as in the lung of experimental animal models exposed to cigarette smoke (D'hulst et al, 2005;Yao et al, 2008;Braber et al, 2010). Cigarette smoke (either as gas phase or aqueous extract) acutely stimulates the release of interleukin-8 (IL-8) and tumour necrosis factor-a in macrophages (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular basis of susceptibility of mouse strains to effects of CS is not known. Previous studies have demonstrated that C57BL/6J mice responded to CS exposure with accelerated development of emphysema [1,2,3,4,5] while those of the strain 129S2/SvHsd, which produce low levels of tumor necrosis factoralpha (TNF-a), were resistant to lung inflammation and oxidant responses to CS exposure [4,5] showing no inflammatory response to smoke at 24 h [6].…”
Section: Introductionmentioning
confidence: 99%